Harvested Rainwater Quality: A Case Study Of Aule In Akure, South Western Nigeria - Ochuko Mary Ojo (European Scientific Journal, ESJ, 2016)
The quality of harvested rainwater in Aule area of Akure, South western Nigeria was assessed in this study. Water samples were collected from 25 rain water storage tanks within the study area and a well was used as a control. The water samples were subjected to detailed laboratory analysis and the results obtained was compared with World Health Organization (WHO) standard for drinking water. The turbidity values ranged from 2.7 to 9.1 NTU for the harvested rainwater samples while the well water sample had a turbidity of 2.3 NTU. The conductivity values for the rainwater samples ranged from 101 to 1328 Ωs/cm. The conductivity value was lower in the well water (164 Ωs/cm) than in most of the harvested rain water samples. The pH of the harvested rainwater ranged from 6.1 to 7.4 with 36 % of the water samples having a pH less than the WHO minimum limit of 6.5. The pH of the well water sample was 7.4 and was within the WHO acceptable limits of 6.5 to 8.5. All the sampled rainwaters and well water had bacteria in them. The total bacterial content of the rain water samples ranged from 05 to 28 CFU/100 mL, while that of the well was 05 CFU/100 mL. The total coliform contents of the rainwater samples ranged from 03 to 18 CFU/100 mL, while that of the well was 02 CFU/ 100 mL. Based on the results obtained from this study, it is recommended that harvested rainwater be treated to kill contaminating microorganisms and to reduce the health risks associated with its consumption.